The Ideological Construction of The 2015 Paris Attacks in The Jakarta Post - Nurzakiyah, Nafisah; Mujiyanto, Januarius; Sutopo, Djoko (English Education Journal, 2019)
The terrorist attacks makes the global phenomenon in the world as the radical action by terrorist group. Therefore, this study wants to find out the ideological constuction of the 2015 Paris attacks in the Jakarta Post. The writer analyzed the data by using Critical Discourse Analysis which is proposed by van Dijk. This theory known as socio-cognitive approach which analyzes the object of the study into three levels: text, socio-cognitive, and societal analysis. The expected of the study, the writer applies the qualitative method to observe the study. The finding of this study revealed that The Jakarta Post emphasizes the bomber in Paris is claimed by Islamic group or ISIS. The writer found that ISIS in Paris attacks is depicted as violent group. Therefore, the people around the world cares about this case. From the findings, it was true that the power or dominant group can influence the text to spread the ideology to the society.